Evaluation of Metaverse integration of freight fluidity measurement alternatives using fuzzy Dombi EDAS model. (December 2022) - Deveci, Muhammet; Gokasar, Ilgin; Castillo, Oscar; Daim, Tugrul
Highlights: An extended EDAS method with Dombi function for aggregation is used for the ranking. The Dombi norms based LMAW is used to find the weights of criteria. The proposed model enables DMs to better perceive the relationship between criteria. Three freight fluidity measurements are assessed by 13 criteria and 4 main aspects. Integrating freight activities into Metaverse is the most advantageous one. Abstract: Developments in transportation systems, changes in consumerism trends, and conditions such as COVID-19 have increased both the demand and the load on freight transportation. Since various companies are transporting goods all over the world to evaluate the sustainability, speed, and resiliency of freight transportation systems, data and freight fluidity measurement systems are needed. In this study, an integrated decision-making model is proposed to advantage prioritize the freight fluidity measurement alternatives. The proposed model is composed of two main stages. In the first stage, the Dombi norms based Logarithmic Methodology of Additive Weights (LMAW) is used to find the weights of criteria. In the second phase, an extended Evaluation based on the Distance from Average Solution (EDAS) method with Dombi unction for aggregation is presented to determine the final ranking results of alternatives. Three freight fluidity measurement alternatives are proposed, namely doing nothing, integrating freight activities into Metaverse for measuring fluidity, and forming global governance of freight activities for measuring fluidity through available data. Thirteen criteria, which are grouped under four main aspects namely technology, governance, efficiency, and environmental sustainability, and a case study at which a ground framework is formed for the experts to evaluate the alternatives considering the criteria are used in the multi-criteria decision-making process. The results of the study indicate that integrating freight activities into Metaverse for measuring fluidity is the most advantageous alternative, whereas doing nothing is the least advantageous one.